2011
DOI: 10.1262/jrd.10-163m
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Heat Stress Exposure During Meiotic Maturation on Oocyte, Surrounding Cumulus Cell, and Embryo RNA Populations

Abstract: Abstract. To determine if reductions in developmental competence related to heat stress exposure were correlated with perturbations in certain RNA populations, poly(A) RNA, total RNA, RNA size distribution, and the abundance of transcripts (cyclin B1, GDF9, BMP15, poly(A) polymerase, HSP70, 18S & 28S rRNA) were examined in oocytes matured at 38.5 or 41 C. Performing in vitro fertilization resulted in embryos for examining RNA. Relative to germinal vesiclestage oocytes, total amount of poly(A) RNA decreased sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 82 publications
(88 reference statements)
3
37
0
3
Order By: Relevance
“…Also, Payton et al [52] did not find any significant difference in the relative abundance of BMP15 and GDF9 in germinal vesicle stage and matured oocytes on exposure to 41°C for first 12 h of in vitro maturation. However, the heat-induced perturbations occurring at molecular level during maturation are inherited by later stage embryos even after fertilization [53].…”
Section: Discussionmentioning
confidence: 99%
“…Also, Payton et al [52] did not find any significant difference in the relative abundance of BMP15 and GDF9 in germinal vesicle stage and matured oocytes on exposure to 41°C for first 12 h of in vitro maturation. However, the heat-induced perturbations occurring at molecular level during maturation are inherited by later stage embryos even after fertilization [53].…”
Section: Discussionmentioning
confidence: 99%
“…To validate some of the microarray results, the relative abundance of five transcripts identified as differentially expressed in the cumulus surrounding the control and heatstressed oocytes was examined using cumulus-derived cDNA from a different experimental effort described by Payton et al (2011). In that study, intact cumulus-oocyte complexes were randomly allotted to culture at 38.5 8C for 0 (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, some findings provided evidence for bovine HSO to mature faster than non-heat-stressed counterparts (Edwards et al, 2005;Schrock et al, 2007; Andreu- Vazquez et al, 2010). In agreement with our results, oocytes heat-stressed during the germinal vesicle stage (bovine: Payton et al, 2004;mouse: LaRosa and Downs, 2007) or during maturation (bovine: Ju et al, 2005;Schrock et al, 2007;Edwards et al, 2009;Zhandi et al, 2009;Rispoli et al, 2011;Payton et al, 2011) have shown competence in overcoming the first cellular division similar to that found in non-HSO. In addition, we observed that HS treatment improved the ability of the oocytes to form blastocysts.…”
Section: Discussionsupporting
confidence: 90%